2021
DOI: 10.3390/ijms222010970
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Human Teeth Stem Cells Trigger ATP Release and Promote Migration of Human Microglia through P2X4 Receptor/MFG-E8-Dependent Mechanisms

Abstract: Extracellular vesicles (EVs) effectively suppress neuroinflammation and induce neuroprotective effects in different disease models. However, the mechanisms by which EVs regulate the neuroinflammatory response of microglia remains largely unexplored. Here, we addressed this issue by testing the action of EVs derived from human exfoliated deciduous teeth stem cells (SHEDs) on immortalized human microglial cells. We found that EVs induced a rapid increase in intracellular Ca2+ and promoted significant ATP release… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 42 publications
(68 reference statements)
1
14
0
Order By: Relevance
“…Purinergic signaling plays a crucial role during ATP-induced chemotaxis and phagocytic activity of microglia (Zabala, Vazquez-Villoldo et al 2018) (Ohsawa, Irino et al 2007, Kobayakawa, Ohkawa et al 2019. We have recently showed that EVs promoted the migration of human microglia through the purinergic receptor P2X4 pathway (Jonavice, Romenskaja et al 2021). The present study demonstrates that P2XR4 signaling is indispensable for the EV-induced lipid raft formation in the microglia.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Purinergic signaling plays a crucial role during ATP-induced chemotaxis and phagocytic activity of microglia (Zabala, Vazquez-Villoldo et al 2018) (Ohsawa, Irino et al 2007, Kobayakawa, Ohkawa et al 2019. We have recently showed that EVs promoted the migration of human microglia through the purinergic receptor P2X4 pathway (Jonavice, Romenskaja et al 2021). The present study demonstrates that P2XR4 signaling is indispensable for the EV-induced lipid raft formation in the microglia.…”
Section: Discussionsupporting
confidence: 60%
“…We have recently demonstrated the importance of purinergic receptor P2X4R signaling for EV-induced microglial migration (Jonavice, Romenskaja et al 2021). Purinergic receptors are also enriched in the inflammatory lipid rafts (Garcia-Marcos, Dehaye et al 2009).…”
Section: Inhibition Of P2x4r Prevents Ev-induced Lipid Raft Formation...mentioning
confidence: 99%
“…EVs also induced a rapid increase in intracellular Ca 2+ and ATP release in microglial cells. EVs were also able to promote microglial motility through P2X4 receptor/milk fat globule-epidermal growth factor-factor VIII (MFG-E8)-dependent mechanisms [ 75 ].…”
Section: Dental Stem Cell Secretome Neuroprotective and Neuroregenerative Potential In Preclinical Modelsmentioning
confidence: 99%
“…The mechanisms by which EVs regulate the neuro-inflammation processes of the microglia remain largely unexplored. Recently, the action of EVs derived from human exfoliated deciduous teeth stem cells (SHEDs) (EVs-SHEDs) on human microglial cells has been investigated [ 16 ]. In particular, EVs-SHEDs encourage a rapid increase in the intracellular Ca2+ level, and promote ATP production and microglial migration.…”
mentioning
confidence: 99%
“…In particular, EVs-SHEDs encourage a rapid increase in the intracellular Ca2+ level, and promote ATP production and microglial migration. The results demonstrate that EVs-SHEDs have an immunomodulatory effect and induce microglial motility through P2X4R/MFG-E8-dependent mechanisms [ 16 ].…”
mentioning
confidence: 99%